PENGARUH PEMANFAATAN SARANA DAN PRASARANA PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 3 GRATI SATAP KABUPATEN PASURUAN - Nanik Legiwati (Jurnal Penelitian dan Pendidikan IPS, 2016)
This research aims to know the influence of the use of facilities and infrastructure, learning motivation on learning on learning achievement, and the use of facilities and infrastructure and learning motivation simultaneously on learning achievement of seventh graders at SMPN 3 Grati Pasuruan. Fifty five (55) students were involved as the respondents in this research. As the result, it show that there are significant influence of the use of facilities and infrastructure, learning motivation, and the use of facilities and infrastructure and learning motivation simultaneously on learning achievement of seventh graders at SMPN 3 Grati Pasuruan.